PERLINDUNGAN HUKUM TERHADAP PERLIDUNGAN KONSUMEN PT. GO-JEK INDONESIA DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Nur Muhammad Awaludin (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
AbstractProblems with the use of online transportation services PT. Indonesian go-jek is the awareness of consumers to read the regulations and rights as consumers in the go-jek application is very lacking, therefore in the use of online transportation consumers are always victims and if there are losses caused by drives do not know how to solve them. Therefore the authours are interested in examining what form of legal protection for users of online transportation services PT. Indonesian go-jek in the perspective of law number 8 of 1999 concerning consumer protection and how to resolve disputes caused by drivers. This research is normative legal research that examines the study of documents, which uses a variety of legal matererials such ass statutory regulations, non-legal material in the form of scholars as for the problem of the problem used in this research is the author uses the law approach and approach conceptually. From the results of the study, the authors concluded that there was a form of legal protection for users of online transportation services PT. Indonesia go-jek in the perspective of law number 8 of 1999 concerning consumer protection, namely preventive legal protection with the aim of preventing before the of violations against users of online transportation services PT. Indonesian go-jek, repressive legal protection with the aim to resolve legal protection disputes by the general court. As for how to resolve disputes already regulated in article 47 of law number 8 of 1999 concerning consumer protection, dispute resolution outside the court and dispute resolution through the court are regulated in article 48 of law number 8 of 1999 concerning consumer protection.KEYWORD : LEGAL PROTECTION FOR USERS OF ONLINE TRANSPORTATION SERVICES PT. GOJEK INDONESIAN